(untitled) (Nonconventional Technologies Review, 2022)
The study focused on the impact of 100% non-refundable European funds on new businesses established in Romania through the Start-up Plus and Start-up Diaspora financing programs.In this sense, a standardized questionnaire consisting of 35 questions was designed and applied to a sample of 198 entrepreneurs who benefited from 100% non-refundable financing of approximately 40,000 euros during the years 2019 - 2020. As a result of the validation of all questionnaires completed by the beneficiaries of these types of funding, we used SPSS v.16.0 and SPSS v. 29.0 to interpret the obtained data.The obtained results led us to a series of worrying conclusions regarding the management and sustainability of this type of financial support among newly established enterprises.The result of this research can represent one of the most important starting points for the central public authorities necessary for the development of future funding lines